ENHANCING VOCABULARY SKILLS FOR YOUNG LEARNERS USING CROSSWORD PUZZLE MOBILE GAME - Prayoga, Gede Hermawan Adi (Universitas Muhammadiyah Makassar, 2022)
Vocabulary is a very important skill in learning English. Therefore, effective vocabulary learning is needed to support the development of English. Mobile games are one of the media that can be implemented in vocabulary learning. Mobile games are used because they are fun and can attract students' attention in learning. The use of crossword puzzle games in vocabulary learning is the focus of this study. The crossword game used is based on a mobile game, namely